THE ASSOCIATION BETWEEN SKIPPING BREAKFAST AND GASTROINTESTINAL SYMPTOMS IN ADULTS: A SCOPING REVIEW - Dr. dr. Yenni Zuhairini, M.Gizi, Sp.GK.; Louisa Chiara Citra Halim; Dinda Satya Ranugraha; Azola Syafiq Dida; Kyarra Alifa Putrina; Sharon Colfoort; Fadiya Asla Halilah; Georgius Moreno A.P.; Sulthan Muhammad M.; Faza Ibadurrahman N.; Khansa Mahira; Akhtarania Azizah F.P.; Taufik Hidayatullah (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Background: Skipping Breakfast (SB) is an irregular eating habit with a prevalence of 24% to 87% worldwide, emerging evidence suggests that SB may disrupt gut motility, alter gut microbiota, and influence hormonal balance, which can lead to gastrointestinal (GI) symptoms such as dyspepsia, constipation, and abdominal pain. This study aims to investigate the connection between SB and GI symptoms. Method: We used SB to define the habit of not eating before 11:00 AM at least three times per week and was examined in this scoping review following PRISMA2020 guidelines. A systematic search across six databases (PubMed, Science Direct, Scopus, Wiley, ResearchGate, and ProQuest). Inclusion criteria comprised adult studies (2015–2025) on breakfast skipping and gastrointestinal symptoms. Results: Of 1,286 records screened, 8 met all criteria, with extracted data covering study characteristics, symptom types, and outcomes. SB is consistently linked to GI symptoms i.e.: functional constipation, abdominal pain, bloating. Associations SB with heartburn, gastric acid reflux, diarrhea, and dyspepsia were observed but less consistent. SB is common among young adults, particularly medical students during exam periods, and is associated with increased stress and a higher risk of functional constipation. Reduced meal frequency in SB with dyspepsia may also reduce acid-suppressive therapy effectiveness. However, most studies were cross-sectional and Asian-based, limiting generalizability. Conclusion: Consistent evidence links SB with various gastrointestinal symptoms, suggesting a preventive role for regular morning meals, though further research is needed to confirm causality and clarify underlying mechanisms. Keywords: abdominal pain, constipation, dyspepsia, gastrointestinal symptoms, skipping breakfast